Comparative Analysis of Five Modulus an Pictorial Block Algorithms For Data Hiding in Digital Images - Syandi Nainggolan; Yennimar Yennimar (Institute of Computer Science (IOCS), 2020)
Steganography is an art and science that studies invisible communication from confidential data on a multimedia carrier such as image, audio and video files. The most popular steganography method is the LSB (Least Significant Bit) method. However, the LSB method is very vulnerable to attack by using basic image processing operations. In 2013, Jassim applied the Five Modulus method in the steganography process. Five Modulus method will solve a digital image into a set of image sub-blocks called windows with size n x n. A secret message will be inserted in that window. According to Jassim, the smaller the window size, the more secret messages that can be inserted into the image. Meanwhile, in the Pictorial Block steganography algorithm, the secret information will be stored in a grayscale digital image file and converted to ASCII values ??and the length of the information will be calculated. After that, the digital image will be divided into 2n x 2n blocks using the block truncation coding (BTC) algorithm. Then, the block will be converted to binary format and incorporate the original information on its decomposition matrix. The pictorial block steganography algorithm uses the BTC algorithm to convert the grayscale input image block into a binary image block so that the secret information bit insertion operation can be performed. The resulting steganography software can hide confidential data into a digital image. The secret data stored in the stego image can be extracted out in the extraction process.